(untitled) (Communications in Mathematical Research, 2021)
For a class of elliptic Hessian operators, one type of corresponding parabolic Hessian equations is studied on Riemannian manifolds. The existence and uniqueness of the admissible solution to the first initial boundary value problem for the equations are shown.